2016
DOI: 10.1016/j.ijrobp.2016.06.714
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Statin Use on Outcomes in Triple-Negative Breast Cancer

Abstract: Purpose: We sought to investigate if the use of HMG Co-A reductase inhibitors (statins) has an impact on outcomes among patients with triple negative breast cancer (TNBC). Methods: We reviewed the cases of women with invasive, non-metastatic TNBC, diagnosed 1997-2012. Clinical outcomes were compared based on statin use (defined as ever use during treatment vs. never use). We identified a subset of women for whom a 5-value lipid panel (5VLP) was available, including total cholesterol, low density lipoprotein, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The magnitude of effect reported in that study was similar to what we observed in our analysis, although their findings were likely limited by low power. 32 An association between statins and improved outcomes in patients with breast cancer is biologically plausible. Statins inhibit HMG-CoA reductase (HMGCR), the rate-limiting step in the mevalonate pathway, which is upregulated by mutations in TP53 in breast cancer, including the majority of triple-negative tumors.…”
Section: Cohortmentioning
confidence: 99%
“…The magnitude of effect reported in that study was similar to what we observed in our analysis, although their findings were likely limited by low power. 32 An association between statins and improved outcomes in patients with breast cancer is biologically plausible. Statins inhibit HMG-CoA reductase (HMGCR), the rate-limiting step in the mevalonate pathway, which is upregulated by mutations in TP53 in breast cancer, including the majority of triple-negative tumors.…”
Section: Cohortmentioning
confidence: 99%
“…It was also detected that MCF-7 cells, which are ER + , were not so strongly affected, like MDA-MB231 cells, as the representative for triple negative breast cancer [34]. But their experimental data is contrary to the epidemiological data from Shaitelman et al (2017) [12] which showed no effect of statins in the cohort of triple negative breast cancer patients. MCF7 (2D) MCF7 (3D) Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Epidemiological studies show that the receptor status of patients play an important role for the effectiveness of SVA. Because statin use is not associated with an improved overall survival of triple negative breast cancer patients [12], but a small subset of patients with ER + tumours benefit from the use of statins [7]. It was also detected that MCF-7 cells, which are ER + , were not so strongly affected, like MDA-MB231 cells, as the representative for triple negative breast cancer [34].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the various subtypes of apolipoproteins, apolipoprotein A1 (ApoA1) plays a pivotal role in cholesterol efflux by binding to cellular membrane-bound receptors, including ABCA1 and ABCG1 13 . Several previous studies employed statins, the intensive inhibitors of cholesterol biosynthesis, for breast cancer treatment; however, the beneficial effects are still inconclusive in TNBC [14][15][16] . There is an urgent need to develop more effective therapeutics to manipulate aberrant cholesterol in TNBC.…”
Section: Introductionmentioning
confidence: 99%